The Impact of Corporate Welfare Policy on Firm-Level Productivity: Evidence from Unemployment Insurance - Darrough, Masako N. (Journal of business ethics, 2019)
We study how changes in unemployment risk affect firms’ productivity and whether firm-initiated policies can mitigate the moral hazard problem created by increases in unemployment insurance benefits (UIBs) that might decrease workers’ incentives to work hard. We focus on state-specific changes in UIB levels as a quasi-natural experiment. While a large body of research has examined UIBs, including their effect on unemployed workers, few studies investigate whether UIBs have any impact on a firm’s overall productivity. Using data on firm-level total factor productivity and state-level UIBs, we find a negative association between productivity and UIBs. We also find that the negative association is weaker for firms with higher employee-welfare indices than for firms with lower indices, suggesting that the adverse effect of higher UIBs on productivity is mitigated by policies that benefit workers’ welfare. More specifically, we find that among policies that are under the umbrella of corporate social responsibility, a subset of employee-welfare policies (e.g., work/life benefits) are more effective in managing moral hazard problems than other policies.